Prevalence of Salmonella spp. and Staphylococcus aureus in chicken meat and pork from Cambodian markets - Rortana, C.; Hung Nguyen-Viet; Tum, S.; Unger, Fred; Boqvist, Sofia; Sinh Dang-Xuan; Koam, S.; Grace, Delia; Osbjer, K.; Heng, T.; Sarim, S.; Phirum, O.; et al. (MDPI, 2021)
Salmonella spp. and Staphylococcus aureus are two of the most common foodborne bacteria in animal-source foods (ASF) that cause illness worldwide. This study aimed to determine the prevalence of Salmonella spp. and S. aureus in chicken meat and pork in markets in Cambodia. Sampling was done in 52 traditional markets and 6 supermarkets in 25 provinces of Cambodia between October 2018 and August 2019. In total, 532 samples were obtained: chicken meat and pork (n = 408, 204 of each), chicken and pork cutting board swabs (n = 124, 62 of each). All samples were analyzed for the presence of Salmonella spp. and S. aureus; colony-forming units per gram (CFU/g) of coagulase-positive Staphylococci (CPS) were counted, and a subset of samples was also analyzed for the most probable number (MPN, n = 136) of Salmonella. The overall prevalence of Salmonella spp. and S. aureus were 42.1% (224/532) and 29.1% (155/532), respectively, with 14.7% (78/532) of samples containing both bacteria. The prevalence of Salmonella spp. in chicken meat was 42.6%, on chicken cutting board it was 41.9%, on pork it was 45.1%, and the pork cutting board 30.6%. Chicken meat had a significantly (p-value < 0.05) higher prevalence of S. aureus, 38.2%, compared to the chicken cutting board, 17.7%, pork 28.9%, and pork cutting board 11.3%. Mean MPN-Salmonella was 10.6 MPN/g in chicken and 11.1 MPN/g in pork samples. Average Log CFU/g of CPS in chicken and pork samples were 2.6 and 2.5, respectively. The results indicate that chicken meat and pork in Cambodia were highly contaminated with Salmonella spp. and S. aureus, posing risks to consumers’ health. Urgent interventions are necessary to improve hygiene for safer meat in Cambodian markets.